2001
DOI: 10.1089/153056201316970948
|View full text |Cite
|
Sign up to set email alerts
|

Change of Patients' Perceptions of TeleHomeCare

Abstract: The study's objectives were to measure patients' perceptions of a telehomecare system before and after they have participated in it and identify the features of the system that patients perceived differently after experiencing it. The study setting was the TeleHomeCare Project, which uses videoconferencing and Internet equipment to enable interactions between patients and nurses. An instrument that measures perceptions of telehomecare was used. Patients viewed a videotape that demonstrates a "virtual home care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 10 publications
3
72
0
2
Order By: Relevance
“…However, studies that have examined the acceptability of these new methods after the patients have used them have reported greater acceptability [14][15][16]. Furthermore, there is some evidence that initial reluctance may be overcome by providing patients with the experience of actually using the technology [8,17]. The main challenge in implementing such methods therefore may be to find ways of overcoming patients' initial reluctance sufficiently for them to gain familiarity with them.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies that have examined the acceptability of these new methods after the patients have used them have reported greater acceptability [14][15][16]. Furthermore, there is some evidence that initial reluctance may be overcome by providing patients with the experience of actually using the technology [8,17]. The main challenge in implementing such methods therefore may be to find ways of overcoming patients' initial reluctance sufficiently for them to gain familiarity with them.…”
Section: Discussionmentioning
confidence: 99%
“…16 The psychological benefit is very important to children and adolescents, who are usually apprehensive about hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…19,24 Study participants were comfortable with the use of the technology, 19 and some even reported greater empowerment 21 or increased confidence in managing chronic illness. 26 …”
Section: Effects On Older Adult Patientsmentioning
confidence: 98%